Decline in Prejudice among Church-Goers Following Clergy-Led Open Housing Campaign - Friedrichs, Robert Winslow (Journal for the scientific study of religion, 1971)
A 1959 study of suburban attitudes toward open housing demonstrated the typical findings of relationship between church-going and prejudice: church members were more prejudiced than non-members, and moderate attenders were more prejudiced than either frequent or slight attenders. A six-year follow-up, after vigorous efforts by clergy and others in the community to counteract prejudice among church-goers, yielded substantially different results: church members were less prejudiced than non-members, and moderate attenders were the least prejudiced. Evidence of the "Myrdal dilemma" remained: large percentages still regard segregation as unChristian or undemocratic, but oppose open housing.